2007
DOI: 10.1177/0310057x0703500213
|View full text |Cite
|
Sign up to set email alerts
|

Changing from Epidural to Multimodal Analgesia for Colorectal Laparotomy: An Audit

Abstract: Epidural analgesia has been shown previously to provide better pain relief than opioid-based analgesia for abdominal surgery 1,2. In some types of surgery it has also been demonstrated to improve patient outcome through reduced respiratory impairment 3 , myocardial infarction 4 and venous thromboembolism 5 .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…The 2 most common reasons were fear of litigation and a lack of evidence for beneficial effects. 49 Although serious complications are uncommon, patients should be informed about common adverse effects such as urinary retention and pruritus and should be counseled about the risks of major neurologic complications such as paralysis. The risks and benefits should be assessed on an individual patient basis.…”
Section: Risks Of Epidural Techniquesmentioning
confidence: 99%
“…The 2 most common reasons were fear of litigation and a lack of evidence for beneficial effects. 49 Although serious complications are uncommon, patients should be informed about common adverse effects such as urinary retention and pruritus and should be counseled about the risks of major neurologic complications such as paralysis. The risks and benefits should be assessed on an individual patient basis.…”
Section: Risks Of Epidural Techniquesmentioning
confidence: 99%
“…The efficacy of this practice has been corroborated in a retrospective case control audit of 113 patients having lower abdominal incisions (for colorectal surgery) 12 . Two and a half years of data from both before and after our conversion in 2002 from epidural analgesia to MM was collected and analysed.…”
mentioning
confidence: 87%
“…In addition, with the increased use of low-molecular-weight heparin for deep venous thrombosis prophylaxis, there has been an increase in the incidence of epidural hematoma, primarily in elderly patients (7). A survey of Australian anesthesiologists showed that 82% of them had inserted fewer epidural catheters due to the fear of litigation and a lack of evidence for benefi cial eff ects (8). A good alternative to thoracic epidural analgesia for thoracotomies is paravertebral blocks due to a lower incidence of complications (9).…”
Section: Invited Commentarymentioning
confidence: 99%